THE EFFECT OF GREEN IMAGE ON REVISIT INTENTION MEDIATED BY TRUST AT NIPAH PARK IN MAKASSAR CITY - Kasim, Amalia; Ramli, Anwar; Hasdiansa, Ilma Wulansari (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the effect of green image on revisit intention at Nipah Park with trust as a mediating variable. The main focus of this study is to determine whether the environmentally friendly image of Nipah Park can increase consumer intention to revisit through building consumer trust. This study uses a quantitative approach with a survey method by distributing questionnaires to respondents who meet the criteria. The sample was selected using a purposive sampling technique, with a total of 120 respondents formulated based on the hair formula. The data obtained were analyzed using Partial Least Square (PLS-SEM) based Structural Equation Modeling techniques. The results of the analysis show that green image has a positive and significant direct effect on revisit intention and trust. In addition, trust is also proven to have a positive and significant effect on revisit intention and also mediates the relationship between green image and revisit intention. These findings indicate that trust plays an important role in mediating the influence of green image on consumer visit intention.Keywords: Green Image, Trust, Revisit intention,Nipah Park